The differential dynamic model for the implicit safety culture dissemination in nuclear power plants. Issue 6 (July 2022) - Yuan, Da; Wang, Hanqing; Zhu, Hui; Xiao, Wangping; Yu, Chuck W.
This paper evaluates the implicit safety culture (ISC) and the dissemination among staff in a nuclear power plant. The Schein's cultural hierarchy theory was adopted to compare implicit aspects of different organizational cultures, and to explore the application of both explicit and implicit cultures, to define the ISC of a nuclear plant and to summarize its characteristics. The dissemination system and the mechanism of the ISC was scrutinized based on dynamic and superimposing effects, which are regarded as a unity of opposites. A differential dynamic model of the ISC dissemination of the nuclear power plant was established by this study. Results of the model indicated that the ISC could be disseminated freely within the power plant when the dissemination was at an unstable equilibrium point. However, the ISC would not disseminate effectively and might disappear gradually in the power plant when the dissemination was at an asymptotic equilibrium point. The application of ISC is a crucial issue to improve the safety and benefit of the management of the nuclear power plant, including measures such as intensifying the collaboration and communication of departments, and setting a special department for the ISC dissemination and some incentive protocols in the nuclear power plant.